Malate-Aspartate Shuttle Plays an Important Role in LPS-Induced Neuroinflammation of Mice Due to its Effect on STAT3 Phosphorylation - Zhou, Cuiyan; Shang, Wangsong; Yin, Shan-Kai; Shi, Haibo; Ying, Weihai (Frontiers in Molecular Biosciences, 2021)
Neuroinflammation is a key pathological factor in numerous neurological disorders. Cumulating evidence has indicated critical roles of NAD+/NADH metabolism in multiple major diseases, while the role of malate-aspartate shuttle (MAS) - a major NADH shuttle - in inflammation has remained unclear. In this study we investigated the roles of MAS in LPS-induced neuroinflammation both in vivo and in vitro. Immunofluorescence staining, Western blot assay and Real-time PCR assays were conducted to determine the activation of Iba-1, the protein levels of iNOS and COX2 and the mRNA levels of IL-1β, IL-6, and TNF-α in vivo, showing that both pre-treatment and post-treatment of aminooxyacetic acid (AOAA) - an MAS inhibitor - profoundly decreased the LPS-induced neuroinflammation in mice. BV2 microglia was also used as a cellular model to investigate the mechanisms of this finding, in which such assays as Western blot assay and nitrite assay. Our study further indicated that AOAA produced its effects on LPS-induced microglial activation by its effects on MAS: Pyruvate treatment reversed the effects of AOAA on the cytosolic NAD+/NADH ratio, which also restored the LPS-induced activation of the AOAA-treated microglia. Moreover, the lactate dehydrogenase (LDH) inhibitor GSK2837808A blocked the effects of pyruvate on the AOAA-produced decreases in both the cytosolic NAD+/NADH ratio and LPS-induced microglial activation. Our study has further suggested that AOAA produced inhibition of LPS-induced microglial activation at least partially by decreasing STAT3 phosphorylation. Collectively, our findings have indicated AOAA as a new and effective drug for inhibiting LPS-induced neuroinflammation. Our study has also indicated that MAS is a novel mediator of LPS-induced neuroinflammation due to its capacity to modulate LPS-induced STAT3 phosphorylation, which has further highlighted a critical role of NAD+/NADH metabolism in inflammation.